PARKUS MWD SYSTEM AND APPLICATION EXPERIENCE ON UKRAINE - ANDRUSHCHENKO, V.; KURHANSKYI, V.; PETRUK, M.; TISHAIEV, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Structural configuration and application experience of the first wireless telemetering system on Ukraine with an electromagnetic transmission channel are given.